PENINGKATAN KUALITAS PELAKSANAAN BELANJA DAN PELAPORAN KEUANGAN MELALUI PROGRAM ASISTENSI DANA DESA - Agus Sunarya Sulaeman (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat, 2021)
Village Fund has been launched by the central government for five years. Various problems arise in its management. The problem of human resources of village financial managers becomes an important point, one of the effects is that the problem of shopping administration and financial reporting of villages becomes difficult. The assistance program is carried out to increase the human resources capacity of village financial administration and reporting. This program is carried out by combining classical approaches in the classroom, mentoring in the field and creating a community of village financial managers. Aspects of completeness of administration documents, quality of administration, completeness and quality of reporting are indicators of the success of this program. The results of this assistance program have an impact on increasing the human resources capacity of village financial managers. The basis is the improvement of quality in the indicators used in village financial administration and reporting.